Algorithm‐based pharmacotherapy for first‐episode schizophrenia involuntarily hospitalized: A retrospective analysis of real‐world practice. Issue 1 (19th May 2017) - Yoshimura, Bunta; Sato, Kojiro; Takaki, Manabu; Yamada, Norihito
Abstract : Background: Little is known about the clinical outcomes of severely ill patients with first‐episode schizophrenia spectrum disorders (FES) who are considered to lack the capacity to consent to clinical trials. We investigated the feasibility of an algorithm‐based pharmacotherapy (ABP) and clinical outcomes of patients with FES involuntarily hospitalized and treated with ABP. Methods: We conducted a retrospective chart review of 160 patients admitted involuntarily between October 2012 and October 2015. Our algorithm aimed to delay olanzapine, standardize medications and suggest initiation of clozapine after failure (non‐response or intolerability) of third‐line antipsychotic treatment. The duration of each adequate antipsychotic treatment at optimal dosage was 4 weeks or more. Results: The physician adherence rate to ABP was 95%. Response and remission rates were 76.0% and 48.6% in the first adequate antipsychotic trial (Phase I, n = 146), 62.5% and 25.0% in the second adequate antipsychotic trial (Phase II, n = 32), and 16.7% and 0% in the third adequate antipsychotic trial (Phase III, n = 6). Response and remission rates in the clozapine trial (n = 9) increased to nearly the level of Phase I (66.7% and 44.4%). The treatment‐resistance rate was 8.4% to 10.3%. Conclusions: These findings suggested the validity of ABP and initiation of clozapine for treatment‐resistant psychotic symptoms for even severely ill involuntarily hospitalized patients with FES.